Metodologías cuantitativas: Cálculo del tamaño de muestra con STATA y R - Quispe, Antonio M. (2020)
The calculation of sample size is an essential aspect of the design of quantitative studies. An adequate sample size allows us to determine the minimum number of participants necessary to test our hypothesis of interest. Hence, we can reduce costs, maximize the use of our research resources and guarantee the feasibility of the study. Contradictorily, despite its relevance, very few researchers dominate this skill. This review aims to review the basics of sample size calculation and share Stata and R codes specifically designed to facilitate these calculations.